Deep water parapagurid hermit crabs: their distribution, abundance, population structure and associations in the Southern Benguela - Wright, Amy Grace (Marine Research (MA-RE) Institute, 2017)
The parapagurids Sympagurus dimorphus (Studer, 1883) and Parapagurus bouvieri (Stebbing, 1910) dominate South African deeper-water benthic invertebrate communities. Samples from the 2016 DAFF bi-annual hake demersal research trawl surveys provided data on population structure and morphology. Since these species forego the use of "traditional" gastropod shells in favour of symbiotically-associated Epizoanthus pseudoshells, these data were also used to investigate parameters of pseudoshell association. S. dimorphus to have a female-biased sex ratio of 1:1.5, and P. bouvieri of 1:1. The proportion of males in both species increased with cephalothoracic shield (CL) length. S. dimorphus males had positive allometric major right chelipeds, while P. bouvieri cheliped lengths were positively allometric in males, and negatively allometric in females. All collected P. bouvieri occurred in pseudoshells, but S. dimorphus showed a real shell occupancy rate of 3.39% (n = 38). A positive relationship was found between CL size and real shell occupation frequency (r2 = 0.96). S. dimorphus pseudoshell zoanthid polyps increased in number as a function of both total shell volume (R2 = 0.73) and colony height (R2 = 0.61), with polyps present on every available part of the shell. No such relationship was found for P. bouvieri, presumably because the polyps are distributed in a linear pattern around the back and outside of the pseudoshell. Juvenile parapagurids appear to select for Naticidae original shells, with Euspira napus being the dominant original shell species for both S. dimorphus (45.45 %) and P. bouvieri (39.00 %). Questions are raised about whether these hermits exist along an evolutionary continuum of traditional shell reliance, whereby the species utilise their pseudoshells differently - P. bouvieri appears to show a stronger mutualistic symbiosis with its exclusive pseudoshell species than S. dimorphus, and may have lost the ability to change shelters entirely, utilising the pseudoshell as a brood pouch covering only the abdomen, rather than as a shell in which to retract to escape predation. Data from 1987 - 2014 surveys were used to map the distribution patterns and densities of these species in the southern Benguela, and to investigate changes in the populations over time. As it stands, no correction factor need be applied to South African parapagurid catches as a result of the 2003-2004 change in survey gear. However, further work is needed. S. dimorphus occurred at a significantly greater mean sample mass (287.88 kg.km⁻²) than P. bouvieri (31.37 kg.km⁻²). The bulk of sample mass occurred within the West Coast Benguela upwelling region, with very few parapagurids caught over the Agulhas Bank, which may be too shallow for either species, given that S. dimorphus showed a preferential depth range of 200 - 299 m (range 30 - 814 m) and P. bouvieri of 400 - 499 m (range 62 - 700 m). The highest mean sample masses occurred on muddy sand (61.00 kg.km⁻²) and sandy sediments (45.68 kg.km⁻²). Overall catchability (mean = 43.35%) has remained constant over the 23 years (R2 = 0.13) with a slight trend towards increasing catchability over time, which may correspond to a change in survey design.